Study On Mathematical Model In Simulating Cymbopogon Winterianus Essential Oil Extraction By Steam Distillation - Nik Amirah Farhana, Nik Ahmad Lutfi; Mohd Farid, Atan; Nazeri, Abdul Rahman; Shanti Faridah, Salleh; Noraziah, Abdul Wahab (JASPE, 2016)
The main objective of this study is to improve the mathematical modelling of Cymbopogon winterianus essential oil extraction by steam distillation proposed by Cassel and Vargas by minimum 5% error reduction. Two process variable of steam distillation which are extraction time and raw material state (dry or natural) has been optimized by using factorial experimental planning to obtain high yields of citronella essential oil from twig and leaves of lemongrass species Cymbopogon winterianus (C.winterianus). The optimal condition for maximum yield (0.942%) were found to be an extraction time, 4 hr, state, natural plant. The study of Cassel and Vargas was subsequently continued with five proposed kinetics model of the extraction process. The modelling of the extraction process is optimized by using one adjustable parameter of the model and the adequacy of the fit of the models to the experimental data are analyzed by using three statistical criteria that are correlation coefficient (r) ,the root mean square error (RMSE) and the mean relative deviation modulus (E). The result has shown that the mathematical model developed by Ana based on mass transfer fundamentals is the optimum mathematical model for the extraction of Cymbopogon winterianus essential oil by steam distillation.